2022
DOI: 10.1177/23259671221121333
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Anatomy of the Humeral Attachment of the Pectoralis Major Muscle and Structures at Risk: A Cadaveric Study

Abstract: Background: Surgical pectoralis major (PM) repair can offer improved functional outcomes over nonoperative treatment. However, there is a lack of literature on consensus of the anatomical site of the humeral attachment. Purpose: To provide qualitative and quantitative anatomic analysis of the PM by focusing on humeral insertion and relevant structures at risk. Study Design: Descriptive laboratory study. Methods: Eight fresh-frozen male cadavers were dissected. The relevant landmarks that were collected and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 22 , 24 This may explain why excessive eccentric loading during weightlifting with the shoulder abducted and externally rotated, such as when performing bench press, is one of the most common mechanisms of injury resulting in PM tears. 10 , 16 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 24 This may explain why excessive eccentric loading during weightlifting with the shoulder abducted and externally rotated, such as when performing bench press, is one of the most common mechanisms of injury resulting in PM tears. 10 , 16 , 22 …”
Section: Discussionmentioning
confidence: 99%
“… 9 , 24 Measurement of the mean distance from the superior to inferior aspect of the humeral footprint revealed that the SH insertion of the PM tendon was located at a distance of 42.1 mm, while the CH insertion was located at a mean distance of 56.6 mm. 10 At the level of the MTJ, the 2 heads were fused, and the CH insertion was found to be longer than the SH insertion, measuring 56.6 mm and 42.1 mm, respectively. Additionally, a tendon overlap footprint length of 27.9 mm was observed.…”
mentioning
confidence: 94%